2022
DOI: 10.2460/ajvr.22.05.0095
|View full text |Cite
|
Sign up to set email alerts
|

A novel vaccine candidate against rabbit hemorrhagic disease virus 2 (RHDV2) confers protection in domestic rabbits

Abstract: OBJECTIVE To evaluate efficacy of a novel vaccine against rabbit hemorrhagic disease virus 2 (RHDV2) in domestic rabbits. ANIMALS 40 New Zealand White rabbits obtained from a commercial breeder. PROCEDURES Rabbits were vaccinated and held at the production facility for the duration of the vaccination phase and transferred to Colorado State University for challenge with RHDV2. Rabbits were challenged with oral suspensions containing infectious virus and monitored for clinical disease for up to 10 days. Rabb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The ongoing local sharing of RHDV2 strains between domestic and wild rabbits in Europe may potentially drive the evolution of the virus, increasing the average virulence of RHDV2 [ 57 ]. In Europe, both Spain and France have licensed highly effective inactivated vaccines to combat RHDV2 [ 58 ]. Regular and organized vaccination efforts against RHDV2 are crucial for controlling the spread and evolution of RHDV2 in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…The ongoing local sharing of RHDV2 strains between domestic and wild rabbits in Europe may potentially drive the evolution of the virus, increasing the average virulence of RHDV2 [ 57 ]. In Europe, both Spain and France have licensed highly effective inactivated vaccines to combat RHDV2 [ 58 ]. Regular and organized vaccination efforts against RHDV2 are crucial for controlling the spread and evolution of RHDV2 in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…The vaccine being tested is a commercially available inactivated (killed) baculovirus-derived recombinant subunit vaccine, directed at eliciting an immune response to the immunogenic VP60 protein of US strains of RHDV2 (patent pending). The complete nucleotide sequence for the VP60 protein has been previously published [ 26 ] and was obtained from the United States Department of Agriculture (USDA) Animal and Plant Health Inspection Service (APHIS) from the circulating strain in 2020. The recombinant VP60 is adjuvanted with aluminum hydroxide to further stimulate the immune response in this proprietary product.…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, recombinant technology does not require that the virulent virus to be passaged and harvested from animals, making this option both safer and more efficient [ 15 ]. Previously, we demonstrated that a baculovirus expressing VP60 provides protection against challenge with RHDV2 in rabbits following a two-dose prime-boost regimen [ 26 ]. Consequently, that vaccine has been available for emergency use for high-risk rabbits and conditionally licensed in the U.S.…”
Section: Introductionmentioning
confidence: 99%
“…The vaccine being tested is a commercially available inactivated (killed) baculovirusderived recombinant subunit vaccine, directed at eliciting an immune response to the immunogenic VP60 protein of US strains of RHDV2 (patent pending). The complete nucleotide sequence for the VP60 protein has been previously published [26] and was obtained from the United States Department of Agriculture (USDA) Animal and Plant Health Inspection Service (APHIS) from the circulating strain in 2020. The recombinant VP60 is adjuvanted with aluminum hydroxide to further stimulate the immune response in this proprietary product.…”
Section: Vaccine Preparationmentioning
confidence: 99%